Karakteristik Ekstrak Kulit Buah Kakao Sebagai Pewarna Alami Pada Variasi Ukuran Partikel dan Lama Ekstraksi Dengan Metode Microwave Assisted Extraction - Maharani, Dwi Nanda Arta; Putra, Gusti Putu Ganda; Antara , Nyoman Semadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Cocoa pods husk contain natural dyes, namely flavonoids, tannins and saponins that can be used as natural dyes. To utilize these dyes, it is necessary to separate them by extraction. Microwave Assisted Extraction is one method to extract color compounds. This study aims to determine the effect of particle size and time of extraction using the Microwave Assisted Extraction method on the characteristics of cocoa pod husk extract and determine the best treatment combination that can produce cocoa pod husk extract as a source of natural color. This study used a Randomized Block Design (RBD) with a two-factor factorial experiment, namely particle size (40, 60 and 80 mesh) and time of extraction (2, 4, 6, 8 and 10 minutes). The data obtained were analyzed by analysis of variance and continued with Tukey test. The results showed that particle size and time of extraction influenced yield, total flavonoids, color intensity (L*, a*, b*), color scoring and overall acceptance. The interaction between treatments significantly affected yield, total flavonoids, color intensity (L*, a*, b*), but had no significant effect on color scoring and overall acceptance. Based on the effectiveness index test, 80 mesh particle size and time of extraction 10 minutes is the best treatment to produce extracts as colorants, with characteristics of yield 7.34 ± 0.17%, total flavonoids 23.41 ± 0.05 mg QE/g, brightness level (L*) 10.76 ± 0.31, redness level (a*) 18.20 ± 0.06, yellowness level (b*) 19.83 ± 0.16, color scoring 4.55 (moderately bright brown - bright brown), and overall acceptance 4.70 (mildly like - like).